In vitro antibacterial activity of fruit pulp extracts of Tamarindus indica against Staphylococcus aureus and Klebsiella pneumoniae - Gatluak Goanar; Geremew Tafesse; Workineh Mengesha Fereja (BMC Complementary Medicine and Therapies, 2024)
Abstract Background Infectious diseases are increasingly recognized as public health concern worldwide as the rising incidence in multidrug resistance bacteria. This consequently enforces the need to find a new antimicrobial agent where plants have a potential source. This study investigated the antibacterial activity of fruit pulp extract of the Tamarindus indica against Staphylococcus aureus (S. aureus) and Klebsiella pneumoniae (K. pneumoniae). Methods and materials Maceration technique was employed for subsequent extraction of the sample using acetone and ethanol. Antibacterial activity of the plant extract was investigated based on minimum inhibitory concentration (MIC) against Gram-negative strain (K. pneumoniae (ATCC 700603)) and Gram-positive strain (S. aureus (ATCC 25923)) using agar disc-diffusion technique. Results It was found that both acetone and ethanol extracts showed significant antibacterial activities, against both S. aureus and K. pneumoniae as compared to the negative control (P = 0.00), but no significantly different from the drug (P > 0.05). However, K. pneumoniae showed more sensitivity to the extracts than S. aureus with MIC value of 18.75 mg/mL and 9.38 mg/mL for both acetone and ethanol extracts against S. aureus and K. pneumoniae respectively. Conclusion This study suggested that the fruit pulp have antibacterial properties, which might validate their traditional uses.